ASSESSMENT OF ENERGY EFFICIENCY OF EXISTING MULTI-APARTMENT RESIDENTIAL BUILDINGS USING THERMAL IMAGING AND HEAT BALANCE ANALYSIS (CASE STUDY OF FERGANA CITY) - Khalimov Abbosbek Oybek ugli (Western European Studies, 2026)
Improving the energy efficiency of existing residential buildings is one of the key challenges in regions with continental climates. This study assesses the current energy performance of typical multi-apartment buildings in Fergana City, Uzbekistan, using nondestructive thermal diagnostics and heat balance calculations. Thermal imaging surveys, air velocity measurements, and indoor microclimate monitoring were conducted to identify heat loss zones and evaluate the thermal resistance of building envelope elements. Two representative buildings—a four-story large-panel reinforced concrete building and a two-story brick building—were analyzed. The calculated thermal resistance values of external walls, windows, roofs, doors, and basement slabs were compared with regulatory requirements. The results indicate that all major envelope components significantly deviate from normative values, leading to excessive heat losses and high specific heat consumption (83.7 W/m²), which exceeds the standard by 46.8%. The investigated panel building was classified as energy efficiency class G. The findings highlight the urgent need for thermal modernization measures, including insulation upgrades and airtightness improvements, to reduce energy consumption and enhance indoor thermal comfort
Keywords: energy efficiency; thermal imaging; residential buildings